Peran Lembaga Bantuan Hukum Di Minahasa Utara Menurut UU NO. 16 tahun 2011 Tentang Bantuan Hukum Dalam Mewujudkan Akses Terhadap Keadilan - Pelealu, Oktaviani Selyn; Wilhellmus, Krisman; Mataliwutan, Welly (SENGKUNI Journal (Social Science and Humanities Studies), 2025)
This study discusses the implementation of Law No. 16 of 2011 on Legal Aid in North Minahasa, which still faces various structural and technical challenges. Three main issues identified are: the very limited number of advocates, the lack of socialization regarding the right to free legal aid, and the minimal allocation of funds for legal assistance and advocacy activities. The methodology used in this study is a normative juridical approach, examining the legal principles and relevant regulations. The focus of the study is on how legal aid is implemented in accordance with the mandates of the law and to what extent the role of Legal Aid Organizations (LBH) ensures access to justice for underprivileged communities in North Minahasa. In the context of human rights, legal principles play an important role in ensuring that every citizen receives fair legal protection. Therefore, collaboration between the government, LBH, advocacy organizations, academics, and civil society is necessary to make the legal aid system more inclusive, transparent, and sustainable. If these challenges can be systematically addressed, the principle of access to justice can be effectively realized in the practice of the Indonesian legal system.